Vaginal and Laparoscopic hysterectomy as an outpatient procedure: A systematic review. (September 2017) - Dedden, Suzanne J.; Geomini, Peggy M.A.J.; Huirne, Judith A.F.; Bongers, Marlies Y.
Abstract: Objectives: Laparoscopic and vaginal hysterectomies are common gynaecological procedures. Same-day discharge is usual care in various gynaecological procedures like laparoscopic sterilisation and laparoscopic oophorectomies. In major procedures like vaginal or laparoscopic hysterectomy patients are usually admitted overnight. We systematically reviewed the literature to identify complications, risk factors for (re)admittance, financial consequences and patient satisfaction of same-day discharge after a vaginal or laparoscopic hysterectomy. Methods: We systematically searched PubMed, UptoDate, Embase, Cochrane and CINAHL database from inception until July 16th 2016. We selected randomized controlled trials, prospective and retrospective cohort studies assessing the safety and feasibility of same-day discharge after vaginal or laparoscopic hysterectomy. The outcome parameters that were assessed were admission rate, re-admission rate, minor and major complications, patient satisfaction and financial consequences. Results: 27 articles were included in the systematic review. All studies provided data about the admission rate and therefore failure of same-day discharge. Eleven prospective studies were included which compromised a total of 2391 hysterectomies. The percentage of overnight admissions was median 9.3% [0–25%]. Eight retrospective studies, which screened their patients before undergoing an outpatient hysterectomy, showed in 1500 subjects a mean admission rate of 10% [4, 4–64%]. Four retrospective studies, which considered a large total cohort of 142, 799 hysterectomies had a mean admission rate of 59, 7% [48–79%]. The overall re-admission rate was low, varying from 0.73–4.0%. Minor complications were reported in respectively 4, 3% and 7, 3% in prospective respectively retrospective trials. Major complications were described in 0.7%–3.6% of all cases. Generally high satisfaction rates were reported in the observational trials. Conclusions: Same-day discharge after laparoscopic and vaginal hysterectomy seems feasible in a pre-selected, healthy population. It is associated with a low (re)admission rate, low complication rate and a reduction in hospital costs. Patient satisfaction seems generally high.